EFFECTS OF GROUPING OF PRINTED DIGITS ON FORCED-PACED MANUAL ENTRY PERFORMANCE. - Klemmer, E. T.; Stocker, L. P. (Journal of Applied Psychology)
Previous studies have shown that optimum grouping of printed digits leads to increased speed in keyboard entry, but differences in error rate due to grouping have generally failed to reach statistical significance. The present study presented numbers to be keyed at a forced-paced rate, chosen separately for each subject from his self-paced rate so as to provide moderate speed stress. Under this condition (n = 18), the error rate was doubled by using a 1-5-1 grouping of seven-digit numbers as opposed to a 3-4 grouping. For five-digit numbers, which cannot be grouped by 3s and 4s, no significant difference in performance was found (n = 24) between 3-2 grouping and ungrouped presentation.